Core Legal Challenges in Determining Locus and Tempus Delicti of Revenge Porn in Indonesia - Wibowo, Aldo Satrio; Sumardiana, Benny (Reformasi Hukum, 2025)
The development of information technology has given rise to new forms of crime, one of which is the offense of revenge porn. In such cases, determining locus delicti (place of the crime) and tempus delicti (time of the crime) poses serious challenges, as content dissemination can occur rapidly, anonymously, and across multiple jurisdictions. This complicates law enforcement efforts in determining jurisdiction, the validity of charges, and the effectiveness of the evidentiary process. This study aims to analyze the implications of revenge porn in Indonesia and the mechanisms and doctrines used in determining locus and tempus delicti in the context of law enforcement. The method employed in this research is normative juridical, using statutory and doctrinal approaches. The results show that determining locus and tempus delicti in revenge porn cases is a crucial aspect of criminal procedural law, particularly given the technological complexities of the present era. Relevant theories, such as the theory of the operation of tools, can be applied to Article 8 of the Electronic Information and Transactions Law (ITE Law) to establish the time and place of a crime juridically. In conclusion, additional regulations addressing the element of revenge and implementing the right to be forgotten are necessary to strengthen the legal framework and address the future challenges of cybercrime in Indonesia.